PERLINDUNGAN PETIR, SISTEM PENTANAHAN, DAN RESISTIVITAS TANAH: STUDI BIBLIOMETRIK - Jakah, Jakah; Muslim, Dicky; Mursito, Anggoro; Zakaria, Zufialdi; Sumarnadi, Eko (BACA: Jurnal Dokumentasi dan Informasi, 2021)
Increased lightning intensity generally causes an increase in the level of hazards such as infrastructure damage and death. To mitigate these hazards, research is necessary. Research developments can be seen from the various literature published in journals or books. This study aimed to quantitatively assess the development of research on lightning protection, grounding systems, and soil resistivity. The bibliometric method is used by searching based on keywords in the Scopus basis data, then visualizing it using VOSviewer. The results showed that the total identified publications were 706 publications all years, the first publication in 1967 and the highest in 2014-2020 with 481 publications (68.1%). The countries that dominate are China and Brazil. Universidade Federal de Minas Gerais was the most productive institution, while Silverio Visacro was the most productive writer. Engineering and energy are the most widely written subjects, while topics related to multidisciplinary are still rare (0.2%). Electric Power Systems Research Journal is the top journal that publishes this research topic. The publication progress map based on co-occurrences consists of 9 clusters. The few research topics include electrical safety, substation, and backfill materials, while current topics include towers, wind turbines, bentonite, natural enhancement materials, and electromagnetic models.